Impact of Self-Assessment on Students’ Oral Production - Mindiola Lozano, Omar Andres (2024)
During the journey of learning a new language, learners tend to have one obstacle in common, and that is to speak fluently. Speaking in English as a foreign language is a complex and multidimensional phenomenon; thus, providing a concise definition for it is very hard (Bygate, 2009; Thornbury & Slade, 2006). The lack of opportunities to use a foreign language in a realistic context, the limited skills when trying to communicate orally, are some difficulties that learners find hard to overcome. Self-assessment is an alternative way of learning and has evolved and became a way of developing speaking skills and making learners more confident. The speaking part has always been one of the most difficult to develop due to the lack of plans or activities that sometimes are not part of the syllabus, learners get frustrated when they have to face a situation, and they do not know how to handle it because they have never practiced in class. Learning and using English has become a necessity, and it is no longer a privilege, the ability to speak a foreign language is a complex task therefore it is difficult for every learner to speak that language fluently and appropriately. That is why this study demonstrated that self-assessment can improve speaking fluency and help learners with the difficulties they face while having a conversation, through explanations, workshops and activities aimed to get better results and become autonomous.